LEGAL APPROACH IN OVERCOMING BAD CREDIT MORTGAGE AT BANK BTN PAREPARE - Akil, Bahrul Iman; Syahril, Muh. Akbar Fhad; Rahman, Muhammad; Ambarwati, Auliah; Asriani, Asriani; Bahtiyor, Kobulov (Sabtida, 2025)
Home Ownership Loans (KPR) offered by PT Bank Tabungan Negara (persero) Tbk. (Bank BTN) are superior products in housing financing. However, the risk of bad loans remains a significant challenge for banks. To overcome this problem, Bank BTN has developed a series of bad loan settlement mechanisms regulated in the Standard Operating Procedures (SOP). These mechanisms include repayment with relief, gradual repayment, transfer of debtors, redemption of collateral, subrogation, cessie, and sale of collateral. Through a transparent and collaborative approach, the bank strives to provide fair solutions for customers and maintain financial stability. The study also identifies factors that affect the success of the non-performing loan settlement process, including policy innovations that accommodate provisions outside the SOP. One such innovation is the transfer of debtors under the hands, which allows risk mitigation and legal protection for potential buyers. Thus, Bank BTN can continue to maintain credit quality and provide the best service to its customers.